1996
DOI: 10.1071/mf9960261
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Observations on Development of Pacific Bluefin Tuna Thunnus thynnus (Scombridae) Larvae Reared in the Laboratory, with Special Reference to the Digestive System

Abstract: Pacific bluefin tuna larvae (Thunnus thynnus) were experimentally reared from 2-day-old yolk-sac larvae through 30-day-old early juveniles in June and July 1994. The larvae initially fed on rotifers on Day 3 and Artemia nauplii, fish eggs and larvae around Day 13, and thereafter were fed Artemia larvae and an artificial diet. The larvae had transformed to the juvenile stage after 30 days. The primitive digestive system differentiated on Day 3. The gastric gland and pyloric caeca first appeared on Day 11 and 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
55
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 0 publications
9
55
0
1
Order By: Relevance
“…In studies focusing on the analysis of nutritional status of tuna larvae, the existing techniques have tended towards histological methods, mainly focusing on histological characteristics and appearance of the digestive tract (Margulies, 1993;Kaji et al, 1996Kaji et al, , 1999. However, nutritional condition studies by nucleic acid and protein content estimation are practically lacking in larval tuna.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies focusing on the analysis of nutritional status of tuna larvae, the existing techniques have tended towards histological methods, mainly focusing on histological characteristics and appearance of the digestive tract (Margulies, 1993;Kaji et al, 1996Kaji et al, , 1999. However, nutritional condition studies by nucleic acid and protein content estimation are practically lacking in larval tuna.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have used histological methods to track the nutritional status of tuna larvae (Margulies, 1993;Kaji et al, 1996Kaji et al, , 1999. The only study in which nucleic acid and protein content was analysed refers to the species T. maccoyi (Carter et al, 1998), for which the differences of specific growth rates and nutritional status in farmed juveniles subject to diet variations were assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Most marine fish larvae have poorly developed digestive systems at first feeding (Sargent et al, 2002), although the larval type-gut has a considerable processing capacity that can support high growth rates, and the adult-type of digestive system (including a functional acid-producing stomach) only develops at metamorphosis, weeks to months after first feeding. However, several studies have revealed that in scombrid larvae such as Spanish mackerel (Scomberomerus niphonius), chub mackerel (Scomber japonicus) and striped bonito (Sarda orientalis), and also NBT and YFT, the adult-type digestive system is established at the mid phase of the larval period or around the first feeding stage, during scombriform-type metamorphosis (Kaji et al, 1996;Miyashita et al, 1998;Kaji et al, 1999;Kaji, 2002;Kaji et al, 2002). Moreover, and in contrast to straight gut teleost fish larvae, bluefin tuna present a rotated gut, which permits retention of ingested food for some time in the anterior midgut, and retrograde peristalsis as a mechanism for filling the pyloric caeca .…”
Section: Early Digestive Capabilitiesmentioning
confidence: 99%
“…Their diet shifts from a more zooplankton-oriented to a piscivorous and even cannibalistic diet already during the early larval stages (Uotani et al 1990, Miyashita et al 2001, Catalán et al 2007, Morote et al 2008). To become a piscivore, the larvae need to have large mouth gapes (Ottera & Folkvord 1993, Folkvord et al 1994, Nishimura & Hoshino 1999, and to develop their digestive (Kaji et al 1996) and visual systems rapidly (Margulies 1997). In fact, the large mouth gape in tuna larvae has been suggested as an adaptive morphological characteristic for a cannibal in the oligo -trophic pelagic environment (Nishimura & Hoshino 1999).…”
Section: Introductionmentioning
confidence: 99%